Childhood cutaneous mastocytosis: Revisited - Bhavya Swarnkar; Rashmi Sarkar (Wolters Kluwer Medknow Publications, 2023)
Cutaneous mastocytosis is a neoplasm characterized by the proliferation and accumulation of mast cells in the skin. There can be involvement of other organ systems as well. Cutaneous manifestations can vary from mastocytoma to maculopapular lesions to diffuse cutaneous form. There can be symptoms associated with mast cell mediators release like itching, flushing, hypotension, diarrhoea, abdominal pain, and anaphylaxis. Hence, the mainstay of treatment is avoidance of triggers causing these mediators to release, anti-histamines, topical/intra-lesional/systemic steroids, mast cell-targeted therapy, epinephrine, and omalizumab depending upon the severity of symptoms/signs. Childhood cases usually have a good prognosis except in a few cases, especially those with systemic involvement. Such situations might warrant cytoreductive therapy, polychemotherapy, or autologous stem cell transplantation. Here, we intend to review the English literature on childhood cutaneous mastocytosis.